Dampak Spillover Antara Harga Komoditas dan Dinamika Pasar Keuangan: Spillover Effect Between Food Commodity Prices and Financial Market Dynamics - Linda Karlina Sari; Agustina Widi Palupiningrum; Ani Nuraisyah (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Interconnectedness among finacial and commodity prices beyond what can be explained by fundamentals, saw a significant rise from 2004 to 2008, reaching their highest point during the global financial crisis. The problem of this research addresses the increasing interdependence and volatility caused by financialization.Purpose: This study examines the complex spillover effects between financial markets and commodity prices from January 2021 to March 2024.Design/methodology/approach: This study employs two approaches: a qualitative approach through a systematic literature review (SLR) and a quantitative approach. Using data from major stock indices and key, we employed Vector Autoregressive (VAR) models to analyze the dynamics.Findings/Result: The study literature indicates a lack of research comprehensive analysis of the spillover effects between financial and commodity markets. Results indicate significant impacts of stock market shocks, particularly in the U.S., on energy prices, and the substantial influence of commodity market fluctuations on the Hong Kong stock market. Conclusion: These findings highlight the critical role of financial markets in driving commodity price volatility and emphasize the need for strategic portfolio diversification and robust risk management. Continuous monitoring and adaptive strategies are essential to mitigate cross-market impacts and ensure market stability, providing valuable insights for policymakers and market participants.Originality/value (State of the art): The value of this research lies in its focus on the recent period, its use of a mixed method approach, and its identification of specific impacts of market shocks on different instruments. Keywords: commodity prices, financial markets, spillover effect, systematic literature review, Vector Autoregressive model